Pengelolaan Zakat Melalui Program Rombong Berkah di Dompet Al-Qur’an Indonesia (Tinjauan Undang-Undang Nomor 23 Tahun 2011) - Nusroh, Alfi Chumidafin; Hermawan, Rudi (Fakultas Syariah INSURI Ponorogo, 2023)
Zakat is one of the obligations in religion that can be imposed on its followers, so that it can be distributed evenly, fairly and efficiently. The distribution and utilization of productive zakat in the Indonesian Al-Qur'an Wallet (DQ) Sidoarjo is channeled through economic empowerment programs, one of which is through this blessing group. This research uses qualitative research, namely field research. In this research, the approach used is normative empirical, the researcher goes directly to see the actual conditions in the field, then identifies the application of normative law. Data collection was obtained from primary sources in the form of interviews with Dompet Al-Qur'an Indonesia (DQ) Sidoarjo and direct location observations, while secondary sources such as books, journals and documents related to rombong bekah. The research findings show that observations of Law Number 23 of 2011 concerning Management of the Sidoarjo Indonesian Al-Qur'an Wallet Zakat (DQ) in optimizing the management practices of the rombong blessing zakat program have carried out several stages, namely submission, assessment, decision making, mentoring and evaluation. However, this practice is still not effective in increasing the income, standard of living and welfare of the people of Sidoarjo as stated in article 3 (b) of Law Number 23 of 2011 concerning Zakat Management.